The BEHEALTH Intelligent Mentoring Tool for Quality Improvement in Nursing Education: A Pilot Demonstration - Kristína Zgodavová; Peter Bober; Aleš Bourek; Juliana Gabzdilová; Jozef Babečka (Quality Innovation Prosperity, 2026)
Purpose: The purpose of this paper is to introduce the BEHEALTH Intelligent Mentoring Tool (IMT) and demonstrate its operational feasibility and analytical functionality as a practical decision-support tool for Institution Quality Managers (IQMs) in Nursing Vocational Education and Training (NVET) and Nursing Work-based Learning (NWBL). Methodology/Approach: Rooted in the ENQA ESG (2015) and EQAVET framework (Council of the European Union, 2020), the IMT extends quality assessment by incorporating student mental health and well-being, occupational health and safety, and environmental management. A 360-degree survey on a 1 – 5 scale gathered pilot data from four stakeholder groups: managers, teachers, students, and employers across six European countries. Findings: The pilot testing demonstrated the IMT’s operational feasibility as a decision-support tool for IQMs. The IMT integrated multi-stakeholder assessments, identified perceptual gaps, and generated rule-based feedback to support institutional quality improvement. Research Limitation/Implications: The survey data are intended to demonstrate IMT functionality and should not be used to draw generalisable conclusions. Originality/Value of paper: The paper combines stakeholders’ psychological mental health and well-being metrics with an automated prescriptive expert system for direct institutional action.